Quantitative measurement of impairment in ADHD: perspectives for research and clinical practice (Archives of Clinical Psychiatry, 2014)
Background Functional impairment is needed to make an attention deficit hyperactivity disorder (ADHD) diagnosis, but there is a paucity of instruments addressing this issue. Objective Perform psychometric analysis of a functional impairment scale (FIE). Methods A sample of 320 individuals, including ADHD probands, their siblings and parents, filled the FIE. We analyzed psychometric properties for the entire sample and age groups. Factor structure was determined by a principal component factor analysis, using oblique rotation with Kaiser normalization and Eigenvalues higher than 1. Cronbach’s alpha and Spearman-Brown were calculated. Results Family analysis revealed four components: a) “family life”, b) “self-perception”, c) “performance” and d) “social life”. Adults’ analysis revealed two components: a) “family life, social life and self-perception” and b) “performance”. Children showed the domains: a) “performance and social life”, b) “self-perception” and c) “family life” components. Cronbach’s alpha were above 0.9 in all components. Discussion Results revealed up to four domains depending on the group considered. Different life demands might explain the variability of domains on the groups.